Inhibition of Histone Methyltransferases SUV39H1 and G9a Leads to Neuroprotection in an in vitro Model of Cerebral Ischemia. Issue 10 (October 2015) - Schweizer, Sophie; Harms, Christoph; Lerch, Heike; Flynn, Jennifer; Hecht, Jochen; Yildirim, Ferah; Meisel, Andreas; Märschenz, Stefanie
Cerebral ischemia induces a complex transcriptional response with global changes in gene expression. It is essentially regulated by transcription factors as well as epigenetic players. While it is well known that the inhibition of transcriptionally repressive histone deacetylases leads to neuroprotection, the role of histone methyltransferases in the postischemic transcriptional response remains elusive. We investigated the effects of inhibition of the repressive H3K9 histone methyltransferases SUV39H1 and G9a on neuronal survival, H3K9 promoter signatures and gene expression. Their inhibition either with the specific blocker chaetocin or by use of RNA interference promoted neuronal survival in oxygen glucose deprivation (OGD). Brain-derived neurotrophic factor (BDNF) was upregulated and BDNF promoter regions showed an increase in histone marks characteristic for active transcription. The BDNF blockade with K252a abrogated the protective effect of chaetocin treatment. In conclusion, inhibition of histone methyltransferases SUV39H1 and G9a confers neuroprotection in a model of hypoxic metabolic stress, which is at least in part mediated by BDNF.